2014
DOI: 10.1016/j.bbagen.2014.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Malarial hemozoin: From target to tool

Abstract: Background Malaria is an extremely devastating disease that continues to affect millions of people each year. A distinctive attribute of malaria infected red blood cells is the presence of malarial pigment or so-called hemozoin. Hemozoin is a biocrystal synthesized by Plasmodium and other blood-feeding parasites to avoid the toxicity of free heme derived from the digestion of hemoglobin during invasion of the erythrocytes. Scope of Review Hemozoin is involved in several aspects of the pathology of the diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
179
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(182 citation statements)
references
References 125 publications
2
179
0
1
Order By: Relevance
“…It is generally accepted that the quinoline class of antimalarials (quinine, chloroquine, amodiaquine, and others) work by suppressing hematin crystallization (8,13,21,25,26,28,29). The prevailing hypothesis is that drugs decrease the activity of soluble hematin by forming noncrystallizable complexes (13,30).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally accepted that the quinoline class of antimalarials (quinine, chloroquine, amodiaquine, and others) work by suppressing hematin crystallization (8,13,21,25,26,28,29). The prevailing hypothesis is that drugs decrease the activity of soluble hematin by forming noncrystallizable complexes (13,30).…”
mentioning
confidence: 99%
“…The released heme rapidly oxidizes to Fe(III) hematin, which is toxic to the parasite in its free state (6). The main mechanism of heme detoxification (8) implemented by the parasite is sequestration as nontoxic hemozoin crystals (9)(10)(11)(12) (Fig. 1C).…”
mentioning
confidence: 99%
“…In agreement to this, it was observed that compound 1 but not lapachol, inhibits the b-hematin formation and this may explain the enhanced antimalarial activity of compound 1 versus lapachol. Hemozoin is vital for parasite maintenance 28 . In fact, we observed that most parasite cells were destroyed under compound 1 treatment, suggesting this is a parasiticidal agent.…”
Section: Discussionmentioning
confidence: 99%
“…Heme-interacting molecule may inhibit hemozoin formation (39,40). Thus, to check the effect of these molecules on hemozoin formation, we measured hemozoin formation in vitro by parasite lysate in presence or absence of different BHs.…”
Section: Chemistrymentioning
confidence: 99%